Editorial: From trust in the system to trust in the content - Péter Mezei; Andreea Verteș-Olteanu (Internet Policy Review, 2020)
The internet is the digital reincarnation of a Greek agora or a Roman forum. It works as a "place" for public and private life. As such, it requires reliable, trustful rules to govern the daily routine of its visitors/users. The governance of the internet has gone through a significant (if not tectonic) change since its standardisation. This is clearly reflected by the changes in the concept of trust as well. Historically, trust reflected the concerns of internet users regarding the intrusion of governments into the neutral functioning of this "place". As of now, concerns regarding trust are equally present at the macro and micro level. Trust in platforms and in the content made available through the internet is at the centre of disputes nowadays. This editorial intends to provide for a selected introduction of the macro- and micro-level aspects of trust in the system and trust in the content, including content moderation, copyright law, fake news, game-making, hateful materials, leaking, social media and VPNs.
Keywords: 300; Trust; Internet; Association of Internet Researchers